Use of the Accessory Genome for Characterization and Typing of Acinetobacter baumannii - Turton, Jane F. (American Society for Microbiology, 2011)
Outbreak strains of Acinetobacter baumannii are highly clonal, and cross-infection investigations can be difficult. We sought targets based on AbaR resistance islands and on other genes found in some, but not all, sequenced isolates of A. baumannii among a set of clinical isolates (n = 70) that included multiple representatives of a number of pulsed-field gel electrophoresis (PFGE)-defined types. These included representatives that varied in their profiles at two variable-number tandem repeat (VNTR) loci, which can provide discrimination within a PFGE cluster. Detection, or not, of each element sought provided some degree of discrimination among the set, with the presence or absence of genes coding for a phage terminase (ACICU_02185), a sialic acid synthase (ACICU_00080), a polysaccharide biosynthesis protein (AB57_0094), aphA1, bla(TEM), and integron-associated orfX (Kyoto Encyclopedia of Genes and Genomes [KEGG] no. K03830) proving the most helpful in discriminating between closely related isolates in our panel. The results support VNTR data in describing distinct populations of highly similar isolates. Such analysis, in combination with other typing methods, can inform epidemiological investigations and provide additional characterization of isolates. Most genotypes carrying bla(OXA-23-like) were PCR positive for a yeeA-bla(OXA-23) fragment found in an AbaR4-type island, suggesting that this is widespread.